Thalassemia and Its Problems in the Adolescent Age - I. Wahidiyat; Maria Abdulsalam; A.H. Markum; Muslichan Mz. (Indonesian Pediatric Society, 1983)
Due to better facilities and management in facing thalassemic children it is expected that there will be more surviving patients reaching the adult age. But on the other hand there appears many new problems, such as physical, emotional and social problems. Forty cases of thalassemia major and thalassemia Hb E disease who reached the adult age were discussed in this paper. Face deformity, growth disturbance and skin discoloration were seen in 82,5.%, 95% and 85% of the cases respectively. Inferiority complexes and physical disability were found in about 50% of them. Frequent mild to moderate infections were seen in 25% of the patients. No one suffered from severe or overwhelming infections. Twenty seven (27) out of 40 cases had been splenectomized at the age of more than 5 years. Only 4 cases (10%) showed signs of puberty. The growth disturbance might be due to 2 factors a) failure in maintaining the hemoglobin content at about IO g%, and b) disturbance of gonadotropin hormone due to iron overload. It is therefore highly recommended to put the child at high transfusion regime as early as possible and administer to the child regularly iron chelating agents to prevent the iron overload. Every infection should be promptly eradicated especially in those whose spleen have been removed. Depression which is common among them should be overcome by giving equal opportunities in educations, vocational training and employment. They should be helped to become integrated into adult society.